Mempromosikan Nilai-Nilai Moderasi Islam dalam Mata Pelajaran Bahasa Inggris di MI NU Rowolaku - Muhammad Jauhari Sofi; Nur Hikmah (IIQ An Nur Yogyakarta, 2022)
The values of moderation were very important for young learners. These values were believed to maintain the unity of Indonesia. Therefore, these values were suitable as guidelines for life in all aspects including education. One alternative way to implement Islamic moderation values in education was to internalize them in the learning process, including learning English. This research aimed to explore how to promote Islamic moderation values for MI NU Rowolaku students in English as a foreign language. This research was conducted in grade 3 which consisted of 28 students. This research was a qualitative research. Data were collected using observation and interviews. The results of the research showed that there were five Islamic moderation values promoted by the English teacher at MI NU Rowolaku, namely: tolerance, openness, balance, reasoning that provides space for different opinions, and moderate reasoning does not absolute truth itself.